Technology resistance and globalisation with trade unions: the choice between employment protection and flexicurity - Lommerud, Kjell Erik (2007)
We thank seminar participants at the Norwegian School of Economics and Business Administration, the University of Copenhagen, and the University of Nottingham, for helpful comments and suggestions.